2021
DOI: 10.1155/2021/6468444
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Effect of Partial Replacement of Cement with Bamboo Leaf Ash on Concrete Property

Abstract: Ethiopia’s construction industry is aggressively expanding than ever before. Cement is the most essential and expensive material in this regard. Cement takes 10%–15% by volume of concrete. Nowadays, the construction industry is challenged by the scarcity of cement and price escalation of the cement market. However, scholars try to replace cement with pozzolanic material. Besides this, they investigated that bamboo leaf ash possesses pozzolanic properties. Ethiopia has about 850,000 hectares of lowland bamboo, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…According to the researchers, more than 70% of the oxides of bamboo leaves' ash was silica (SiO 2 , Al 2 O 3 , and Fe 2 O 3 ) followed by a significant amount of CaO, SO 3 , and LOI. e other results of the chemical compositions of BLA by Abebaw et al [21] revealed that SiO 2 , CaO, and Al 2 O 3 were the main oxides, and the LoI was recorded as 9.65%. Asha et al [22] confirm that BLA had 59.20% silicon dioxide which confirms that it has the potential of acting as a pozzolanic material.…”
Section: Materials Characterizationmentioning
confidence: 89%
See 4 more Smart Citations
“…According to the researchers, more than 70% of the oxides of bamboo leaves' ash was silica (SiO 2 , Al 2 O 3 , and Fe 2 O 3 ) followed by a significant amount of CaO, SO 3 , and LOI. e other results of the chemical compositions of BLA by Abebaw et al [21] revealed that SiO 2 , CaO, and Al 2 O 3 were the main oxides, and the LoI was recorded as 9.65%. Asha et al [22] confirm that BLA had 59.20% silicon dioxide which confirms that it has the potential of acting as a pozzolanic material.…”
Section: Materials Characterizationmentioning
confidence: 89%
“…Asha et al [22] confirm that BLA had 59.20% silicon dioxide which confirms that it has the potential of acting as a pozzolanic material. Table 1 summarizes the chemical compositions of BLA based on Frías et al [23]; Rodier et al [24]; Villar-Cociña et al [25]; Moraes et al [1]; Villar-Cociña et al [26]; and Abebaw et al [21]. According to the table and the oxide compositions, all the BLA samples would comply with [27] and characterizes as pozzolans with class N. e higher LOI recorded [1] might be due to the soil and its fertility to grow the bamboo plant and species.…”
Section: Materials Characterizationmentioning
confidence: 99%
See 3 more Smart Citations